Mathematical modeling of the distribution of dust emissions in the spatial structure of the workshop - T. V. Matyushinets; S. Yu. Jatskevich; A. N. Chychko (Литьë и металлургия)
On the basis of mathematical modeling, numerical calculations of the process of forming dust emissions in the workshop containing equipment are performed. The possibilities of obtaining calculated information on the distribution of velocities, temperatures, and dust emissions in a 3d-spatial structure are shown. Calculated three-dimensional dynamics of air and dust in the conditions of the workshop, which can be used to develop activities to improve the ecology of the workshop.